La théologie chrétienne: grammaire subversive au service d'une cité provisoire - Singer, Christophe (Etudes théologiques et religieuses, 2022)
If theological work aims at giving language to the event of faith, then theology can be defined with Luther as the "grammar of the word God". This article explores what this definition implies regarding the possibility of a theology based on experience and Scripture, avoiding the risk of a confessionalism that is hermetic to all dialogue, and thus at the service of a human existence traversed by hope for the Kingdom.